Life in Medieval Shetland: An archaeological Perspective - Bigelow, Gerald F. (Hikuin, 1989)
When the Norse Vikings began long distance voyaging in the late 8th and 9th centuries A.D., Britain was a prominent target. In the three centuries which followed various regions of the British Isles were affected unequally by Viking raiding, trading and landtaking. The Shetland Islands, Britain’s northernmost territory, were probably raided very early, for they are only 340 kilometres from the Norwegian coast. However, the Scandinavians’ greatest influence in Shetland was achieved through intensive colonization. Even today, after five hundred years of British rule and cultural diffusion from Scotland and England, Shetland lifeways still reflect a Norse heritage. Like Greenland and Iceland, Shetland offers archaeologists the opportunity to study the economic, social and biological adaptations that were made by a complex society in a northern island environment. Unlike those western colonies, Shetland also reveals the effects of close proximity to Continental Europe and the large-scale economic and political systems that grew there during the Middle Ages.